A Four-Channel Electrical Impedance Spectroscopy Module for Cortisol Biosensing in Sweat-Based Wearable Applications. (December 2018) - Sankhala, Devangsingh; Muthukumar, Sriram; Prasad, Shalini
A four-channel electrochemical impedance spectroscopy (EIS) analyzer module has been demonstrated on flexible chemi-impedance sensors fabricated with gold electrodes for wearable applications. The module can perform time division multiplexed (TDM) impedance measurements on four sensors at 1 kHz. In this work, we characterize the system for the detection of cortisol in an ultralow volume (1–3 µL) of perspired human sweat, sensor performance, and effects during continuous cortisol dosing and with pH and temperature variations expected on the surface of the skin that would be representative of use conditions as seen by a wearable device. Detection of cortisol was shown for concentrations of 1 pg/mL to 200 ng/mL in both synthetic and perspired human sweat, and output response reported as a change in impedance with varying cortisol concentrations. Continuous dose testing was performed to demonstrate the stability of the sensors over prolonged periods of operation for cortisol concentrations within the physiologically relevant range of 10–200 ng/mL reported in human sweat. Temperature and pH effects testing was performed for pH range 4–8 and in a temperature chamber for the clinical range reported on the surface of human skin: 25–40 °C. The cortisol sensor demonstrated stability of operation with 7.58% variability under these conditions.